UNIDROIT Factoring Model Law: Critiques and Possible Effects - KAYA, barış (Revista Jurídica Portucalense, 2024)
Factoring fulfills an important function globally in financing and accessing credit for businesses, companies and entrepreneurs of all sizes, especially small and medium-sized businesses. The UNIDROIT Factoring Model Law was prepared within a three-year period as a result of the work initiated by UNIDROIT upon the recommendation of the World Bank due to reasons such as the inadequacy of the existing international legislation for countries to create a functional factoring legislation and the need to create global rules and legislation specific to factoring. The UNIDROIT Factoring Model Law for which the Guide to Enactment has not yet been prepared, contains some challenging rules. During the preparation of the UNIDROIT Factoring Model Law, other relevant legal regulations were also used and compliance with them was observed. In this study, the UNIDROIT Factoring Model Law, which is a very new legislation, has been criticized under basic section headings and its weaknesses and strengths have been examined. While doing this, an answer is sought to the question of whether the UNIDROIT Factoring Model Law could meet the expectations. Additionally, its possible effects are discussed. It has been concluded that the UNIDROIT Factoring Model Law contains provisions that may cause problems and confusion in practice especially under the headings of the scope of receivables subject to transfer, notification and registration system, priority rights, but in general it should be welcomed as an exemplary law. It is too early to answer the question of whether the UNIDROIT Factoring Model Law will be successful internationally, that is, to what extent it will be adopted by countries. The Guide to Enactment to be prepared in this process will also be effective.